2015
DOI: 10.1128/iai.02540-14
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of CXCR3 on T Cells Enhances Susceptibility to Cutaneous Leishmania major Infection by Inhibiting Monocyte Maturation and Promoting a Th2 Response

Abstract: e Cutaneous leishmaniasis, caused mainly by Leishmania major, an obligate intracellular parasite, is a disfiguring disease characterized by large skin lesions and is transmitted by a sand fly vector. We previously showed that the chemokine receptor CXCR3 plays a critical role in mediating resistance to cutaneous leishmaniasis caused by Leishmania major. Furthermore, T cells from L. major-susceptible BALB/c but not L. major-resistant C57BL/6 mice fail to efficiently upregulate CXCR3 upon activation. We therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…These results indicated that CXCR3 is important for trafficking of activated T cells into infection sites for the generation of leishmanicidal immune response. Surprisingly when CXCR3 Tg mice were infected with L. major , these mice developed larger lesions characterized by a Th2 skewed immune response [11]. In addition to highlighting the complex role for CXCR3 in progression of leishmaniasis, these studies suggest that resistance is dependent on which T cell subsets undergo CXCR3-mediated activation and home into the lymph nodes and sites of infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results indicated that CXCR3 is important for trafficking of activated T cells into infection sites for the generation of leishmanicidal immune response. Surprisingly when CXCR3 Tg mice were infected with L. major , these mice developed larger lesions characterized by a Th2 skewed immune response [11]. In addition to highlighting the complex role for CXCR3 in progression of leishmaniasis, these studies suggest that resistance is dependent on which T cell subsets undergo CXCR3-mediated activation and home into the lymph nodes and sites of infection.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR3 transgenic mice (CXCR3 Tg ) were generated by the procedure described previously [11]. C57BL/6 CXCR3 Tg were backcrossed to WT BALB/c mice for 10 generations to generate BALB/c CXCR3 Tg mice and BALB/c wild-type littermates (CXCR3 +/+ ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common form is cutaneous leishmaniasis (CL), which causes painless localized skin lesions leading to severe tissue damage and disfigurement without treatment (Varikuti et al, 2017). CL is caused by L. major, L. tropica and L. aethiopica in the old world (Asia and Africa) and L. mexicana and L. braziliensis in the New World (Central and South America) (Oghumu et al, 2015). The most severe form of the disease is Visceral Leishmaniasis (VL) which is mainly caused by L. donovani, L. chagasi and L. infantum (McGwire and Satoskar, 2014).…”
Section: Leishmaniamentioning
confidence: 99%